Ultrasonography of the Vagus Nerve in Parkinson's Disease - Fedtke, Nadin (Front Neurol, 2018)
Based on the topographic distribution of α-synuclein-enriched Lewy bodies, it has been hypothesized that Parkinson's disease may start in the gastrointestinal tract and gain access to the central nervous system via the vagus nerve. Since ultrasonography is a powerful tool to study peripheral nerve disturbances, we conducted ultrasonography of the vagus nerve in 32 patients with Parkinson's disease, 15 disease controls and 15 healthy controls. The cross-sectional area and echogenicity measured on transverse scans of the vagus nerve did not differ significantly between these groups. Therefore, the observed intraneuronal changes in Parkinson's disease are not associated with ultrasonographic disruptions of the vagus nerve integrity. HIGHLIGHTS: We studied ultrasonography of the vagus nerve in 32 patients with Parkinson's disease and in 15 disease controls and 15 healthy controls. The sonographic cross-sectional area measured using high-frequency linear array transducers did not differ significantly between both groups. Ultrasonography of the vagal nerve does not reflect cellular damage caused by α-synuclein-enriched Lewy bodies in nerves of patients with Parkinson's disease.